2016
DOI: 10.1111/peps.12140
|View full text |Cite
|
Sign up to set email alerts
|

Do CEOs Matter to Firm Strategic Actions and Firm Performance? A Meta‐Analytic Investigation Based on Upper Echelons Theory

Abstract: What roles do CEOs play in firm performance? To address this question, the management field has accumulated a substantial amount of research over the past 3 decades built on upper echelons theory (UET), which posits that CEO characteristics manifest in firm strategic actions and, in this way, future firm performance. Hence, there is a need to systematically amass and take stock of prior empirical findings for UET testing and development. We use meta-analytic techniques to synthesize prior UET research on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
373
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(414 citation statements)
references
References 173 publications
(201 reference statements)
22
373
0
19
Order By: Relevance
“…Due to bounded rationality, executives filter and interpret situations based on their personal characteristics (Hambrick & Mason, 1984). Upper echelons research concludes that variance in executive characteristics drives numerous strategic decisions and organization outcomes (see Carpenter, Geletkanycz, & Sanders, 2004, Finkelstein et al, 2009, and Wang, Holmes, Oh, & Zhu, 2016 for reviews). This research is consistent with studies in behavioral finance, which also suggest that individual differences influence how executives' respond to various incentive schemes and, in turn, affect organizational decision-making (Thaler, 2005).…”
Section: Upper Echelons Theorymentioning
confidence: 99%
“…Due to bounded rationality, executives filter and interpret situations based on their personal characteristics (Hambrick & Mason, 1984). Upper echelons research concludes that variance in executive characteristics drives numerous strategic decisions and organization outcomes (see Carpenter, Geletkanycz, & Sanders, 2004, Finkelstein et al, 2009, and Wang, Holmes, Oh, & Zhu, 2016 for reviews). This research is consistent with studies in behavioral finance, which also suggest that individual differences influence how executives' respond to various incentive schemes and, in turn, affect organizational decision-making (Thaler, 2005).…”
Section: Upper Echelons Theorymentioning
confidence: 99%
“…Upper echelons theory (UET) posits that CEO characteristics manifest in the firm's strategic actions and, in this way, its future performance (Wang, Holmes, Oh and Zhu, 2015). The relationship between the TMT and the CEO is an important and intriguing company dynamic that has gained research momentum since Fama and Jensen (1983) described it as the peak of an organization's decision-making system.…”
Section: Tmt Attitudesmentioning
confidence: 99%
“…Grounded on the notions of RDT, the author concluded that all analyzed business members strive to and engage their efforts in the increase in their bargaining power, even if these actions produce modest outcomes. These dissatisfying results, as proposed by UET applied to previous studies [28,29], in this case can be due to the inadequate educational level and ages of the top management of the supply chain actors. The other reason for the low efficacy of the SSC supply chain may be that, as posited by signaling theory, the majority of the investigated members in the supply chain possess very low awareness of the DOL awarded to SSC, and thus do not associate this observable proxy with underlying product perception constructs, such as: Artisan cheese, healthy food, and cultural legacy, as is the usual case for products with PDOs [20,21,31,32].…”
Section: Discussionmentioning
confidence: 76%
“…This theory posits that leaders' experiences, values, and personalities have significant impacts on their perception of the market circumstances, which greatly influence their choices [26,27]. A summary of previous studies [28] revealed that chief executive officer (CEO) characteristics, such as age, tenure, formal education, and prior career experience, are significantly and positively associated with a firm's future performance. Prior research [29] consistently indicated that younger executives and executives with business-related backgrounds are correlated with more innovative and/or sophisticated management systems.…”
Section: Introductionmentioning
confidence: 99%